Benzothiadiazole, a plant defense inducer, negatively regulates sheath blight resistance in Brachypodium distachyon. Issue 1 (December 2018) - Kouzai, Yusuke; Noutoshi, Yoshiteru; Inoue, Komaki; Shimizu, Minami; Onda, Yoshihiko; Mochida, Keiichi
Abstract Plant defense inducers that mimic functions of the plant immune hormone salicylic acid (SA) often affect plant growth. Although benzothiadiazole (BTH), a synthetic analog of SA, has been widely used to protect crops from diseases by inducing plant defense responses, we recently demonstrated that SA, but not BTH, confers resistance againstRhizoctonia solani, the causal agent of sheath blight disease, inBrachypodium distachyon . Here, we demonstrated that BTH compromised the resistance of Bd3-1 and Gaz4, the two sheath blight-resistant accessions ofB .distachyon, which activate SA-dependent signaling following challenge byR .solani . Moreover, upon analyzing our published RNA-seq data fromB .distachyon treated with SA or BTH, we found that BTH specifically induces expression of genes related to chloroplast function and jasmonic acid (JA) signaling, suggesting that BTH attenuatesR .solani resistance by perturbing growth-defense trade-offs and/or by inducing a JA response that may increase susceptibility toR .solani . Our findings demonstrated that BTH does not work as a simple mimic of SA inB .distachyon, and consequently may presumably cause unfavorable side effects through the transcriptional alteration, particularly with respect toR .solani resistance.